Analisis Perilaku Tenaga Kesehatan Terhadap Pelayanan Vaksinasi COVID-19 di Puskesmas Tanjung Agung Tahun 2022 - Putri Mayang Sari; Erma Gustina; Dewi Suryanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
The COVID-19 vaccination provides protection and will reduce the possibility of transmitting the virus to the others and can protect people around the family environment. This study aims to determine what factors were related to the behavior of health workers towards COVID-19 vaccination services at the Tanjung Agung Health Center 2022. The design of this study was an analytical survey with a cross-sectional approach. The population in this study were health workers at the Tanjung Agung Health Center 2022. The sampling method in this study used a total sampling technique. The number of samples in this study were 125 respondents. Data collection by using a questionnaire. The results of statistical test analysis using the chi-square test that showed there was a significant relationship (p value < 0.05) for knowledge (p value 0.015) and motivation (p value 0.026) and there was no relationship between years of service (p value 0.295) and income (p value 0.170). ) on the behavior of health workers towards the COVID-19 vaccination service at the Tanjung Agung Health Center 2022. From the results of the multivariate analysis, the dominant factors on the behavior of health workers towards COVID-19 vaccination services at the Tanjung Agung Health Center 2022 were knowledge (p value 0.017) and (OR 2.833). From this research, it is hoped that health workers at the Puskesmas will increase their knowledge by playing an active role in training and socializing about the administration of COVID-19 vaccination